Synthesis and characterization of diimine compounds, ironacycle and ruthenacycle complexes - Pun, Yean Mee (Universiti Malaysia Sarawak (UNIMAS), 2012)
Luminescent metal complexes such as [Ru(bpy)3] 2+ can be in photosensitizer, organic light-emitting diodes (OLED), solar cell and bioimaging due to its remarkable photophysical property. In most cases, the luminescent metallacycle ruthenium complex were based on the [Ru(bpy)3] 2+. In this project, the phenyl rings at the bpy moiety have been removed to give the 1,4-diaza-1,3-butadiene (dab) moiety. Four dab related compounds have been synthesised and characterised by using 1H NMR, gas chromatography mass spectroscopy (GCMS) and IR spectroscopy. One of the dab related compounds (named compound 1) was reacted to FeCl3·3H2O and RuCl3·nH2O, respectively, to form the respective complexes. The geometry of [FeII(L)2Cl2] and [RuII(L)2Cl2] complexes were proved by the IR, 1H NMR, UV spectroscopy, AgNO3 test and molar conductivity. The differences in the photophysical properties between [FeII(L)2Cl2] and [RuII(L)2Cl2] complexes can be observed in the UV spectra of these two complexes. The [RuII(L)2Cl2] complex exhibited spin forbidden MLCT transition at 706 nm but the [FeII(L)2Cl2] complex did not.